Characteristics of Laterite Nickel Based on Geochemical Data and Electrical Resistivity Tomography (ERT) of Ultramafic Rocks in the Sorowako Area, East Luwu Regency - Patadungan, Erika; Azikin, Busthan; Pachri, Hendra (CV Insight Publisher, 2024)
In laterite nickel exploration, PT.Vale Indonesia Tbk, initialy relied solely on drilling methods to define profile boundaries based on mineral content and rock characteristics, but discrepancies of around 2% between reserve estimates and actual mining outcomes led to the adoption of geophysical methods as a complementary approach in 2014. This study aims to determine the characteristics of laterite nickel profiles by correlating resistivity values with geochemical data. Using Datamine and Leapfrog software, a 3D model of laterite nickel profiles was generated, identifying limonite (0–10 m depth, 201–250 Ohm.m resistivity), saprolite (0–10 m depth, 101–200 Ohm.m resistivity), and bedrock (>10 m depth, 101 to >801 Ohm.m resistivity). Variations in resistivity are influenced by factors such as mineral content and morphology. The volume estimated from resistivity correlation and drillhole data is 1,625,300 m³ for limonite and 1,902,600 m³ for saprolite, compared to 1,523,100 m³ and 1,390,100 m³ based on drillhole-only data, showing discrepancies of 6% and 27%, respectively. This study provides a clearer understanding of geological modeling using drillhole and ERT data to support laterite nickel ore mining and correlation modeling.